Progran Evaluasi Model Praktek Keperawatan Profesional - Elly Nurachmah (Fakultas Ilmu Keperawatan Universitas Indonesia, 1998)
Model praktek keperawatan professional merupakan suatu model yang memberikan kesempatan bagi perawat untuk menunjukkan otonomi dan akuntabilitas dalam memberikan asuhan keperawatan kepada klien. Suatu program evaluasi bagi model praktek keperawatan professional diperlukan untuk mengkaji sejauh mana keefektifan model keperawatan ini terhadap peningkatan pelayanan keperawatan di ruang model ini. Evaluasi dapat diarahkan kepada aspek struktur dimana komitmen organisasi pelayanan keperawatan akan dikaji, aspek proses dimana factor pelibatan dan partisipasi dari seluruh komponen yang terlibat dalam pemberian asuhan keperawatan dinilai, serta aspek hasil dimana kepuasaan klien dapat diukur. Program evaluasi ini seyogyanya dapat dilaksanakan minimal dua kali dalam tiga tahun, dimana evaluasi pertama merupakan informasi dasar bagi evaluasi selanjutnya.Â AbstractA professional nursing practice model is an approach that enables nurses to demonstrate their autonomy and accountability in delivering their care to patients. An evaluation program for a professional nursing practice model is required to assess the effectiveness of this model toward an improvement of nursing service in this model unit. The evaluation plan is involved in three aspects: structure, process, and outcome. The aspect of structure is evaluated to assess a commitment of the nursing service organization. The aspect of process is directed to evaluate an involvement and participation of all components in a nursing care delivery system. And finally, the aspect of outcome is assessed to determine the satisfaction of patients and the staff. A program of evaluation is best to be conducted twice for a period of three years during which the first evaluation is used as a baseline data for an incoming evaluation.Keywords: A professional nursing practice model, a program evaluation, structure, process, outcome.